Move to the rhythm: oscillations in the subthalamic nucleus-external globus pallidus network. - Bevan, MD; Magill, P; Terman, D; Bolam, J; Wilson, C (2002)
Recent anatomical, physiological and computer modeling studies have revealed that oscillatory processes at the levels of single neurons and neuronal networks in the subthalamic nucleus (STN) and external globus pallidus (GPe) are associated with the operation of the basal ganglia in health and in Parkinson's disease (PD). Autonomous oscillation of STN and GPe neurons underlies tonic activity and is important for synaptic integration, whereas abnormal low-frequency rhythmic bursting in the STN and GPe is characteristic of PD. These recent findings provide further support for the view that the basal ganglia use both the pattern and the rate of neuronal activity to encode information.